Dynamical effects in resonant x-ray diffraction - Macke, Sebastian; Keimer, Bernhard; Sawatzky, G. A.; Haverkort, Maurits W. (Physical review letters, 2016)
Using resonant magnetic diffraction at the Ni L2,3 edge in a LaNiO3 superlattice, we show that dynamical effects beyond the standard kinematic approximation can drastically modify the resonant scattering cross section. In particular, the combination of extinction and refraction convert maxima to minima in the azimuthal-angle dependence of the diffracted intensity, which is commonly used to determine orbital and magnetic structures by resonant x-ray diffraction. We provide a comprehensive theoretical description of these effects by numerically solving Maxwell’s equations in three dimensions. The understanding and description of dynamical diffraction enhances the capabilities of resonant x-ray scattering as a probe of electronic ordering phenomena in solids.